2006
DOI: 10.1063/1.2388943
|View full text |Cite
|
Sign up to set email alerts
|

Area-tunable micromirror based on electrowetting actuation of liquid-metal droplets

Abstract: Design, simulation, fabrication, packaging, and characterization of a MEMS-based mirror array for femtosecond pulse-shaping in phase and amplitude Rev. Sci. Instrum. 82, 075106 (2011); 10.1063/1.3606440Actuation of water droplets driven by an organic transistor based inverter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 16 publications
0
32
0
2
Order By: Relevance
“…The material used for insulator has direct effect in asymmetric electrowetting. Parylene has been widely used both in fundamental studies 23,24 and device applications 13,25 of electrowetting. It was reported that while using Parylene as the insulator, the change in contact angle was independent of the polarity.…”
Section: Principle and Fundamental Studies Sessile Drop Experimentsmentioning
confidence: 99%
“…The material used for insulator has direct effect in asymmetric electrowetting. Parylene has been widely used both in fundamental studies 23,24 and device applications 13,25 of electrowetting. It was reported that while using Parylene as the insulator, the change in contact angle was independent of the polarity.…”
Section: Principle and Fundamental Studies Sessile Drop Experimentsmentioning
confidence: 99%
“…EWOD, which is a powerful means to control the electrolyte at micro scale, can change the contact angle and the shape of electrolyte droplet through the electric driving mechanism at the liquid–solid interface. At micro scale, the liquid cohesion and the electrically affected surface tension are dominant, effectively driving the droplet to form convex lens . For an EWOD driven liquid lens, firstly discussed by Peseux and Berge , the voltage applied to the dielectric layer would generate an electrostatic field to change the energy exerted on the liquid–solid interface, and thus reduce the contact angle and change the profile of the electrolyte droplet with electrodes placed at a certain distance from the liquid–solid interface.…”
Section: Adaptive Liquid Lens By Different Methodsmentioning
confidence: 99%
“…Another work related to the control of a boundary profile is the electrowetting-driven area tunable micro mirror (Wan et al 2006), demonstrating optofluidic tunability via modifying the shape of a liquid-gas boundary (a planoconvex mercury droplet and air, Fig. 5).…”
Section: Geometric Tunabilitymentioning
confidence: 99%